Mental fatigue does not impair all-out sprint in elite track cyclists but it alters perceptual responses during continuous submaximal exercise - Staiano, W.; Flyger, N.; Menaspa, P.; Martin, D.; Marcora, S. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
INTRODUCTION: Mental fatigue (MF) has a detrimental effect on endurance performance by altering perceptual responses of effort despite no changes in physiological parameters (Marcora et al., 2009). Moreover, recent studies have proven that MF does not alter anaerobic capacity in a 3 min all out cycling exercise (Martin et al., 2014). The present study had two aims. Firstly, to assess the impact of a cognitive demanding task (Stroop) on anaerobic capacity of elite cyclists during an all-out cycling sprint test (AOS). The second objective was to elucidate the negative effect of MF during a submaximal cycling step test. METHODS: 10 internationally competitive track cyclists completed 30 min of an incongruent Stroop colour-word test, or the equivalent time in a control condition in a cross-over study. Participans completed a submaximal 3-step cycling test (5 min for each step) at a constant power increasing at each step and afterwards they completed a 15 sec AOS. Physiological and perceptual measures of heart rate (HR), cadence (RPM), lactate and rating of perceived exertion (RPE) were collected during the submaximal test and the AOS. Psychological questionnaires were used to assess fatigue and mental demand of the Stroop. RESULTS: The Stroop test was rated as more fatiguing (p<0.001) and mentally demanding (p<0.001) than the control task. There was no significant difference between conditions during the AOS for peak power (p=0.67), mean power (p=0.69) and fatigue index (p=0.96). During the submaximal step test, there were no significant differences between condition for HR (p=0.23), RPM (p=0.88) and lactate (p=0.13). However, a significant interaction time (step) x condition has been reported for RPE (p<0.05). DISCUSSION: No difference in performance between Stroop and control condition suggests that cognitive processes do not regulate maximal anaerobic exercise in AOS for elite cyclists. Anaerobic capacity during AOS seems to be mainly regulated by peripheral parameters. Whereas, 30 min of mentally demanding test negatively impact submaximal endurance exercise during the step test. In line with previous studies, it appears that RPE, is the main variable affected by MF. This is the first study assessing the influence of MF in AOS performance and submaximal exercise in an elite group of track cyclists.